Sustainable development in chemistry education: Few perspectives and practical ideas to support teaching - Marianne Juntunen; Maija Aksela (LUMAT, 2013)
This article presents a 10-point checklist of activities for sustainable development education, and its implementation in chemistry education. The article discusses related research knowledge from the viewpoints of teachers and students. In addition, the article presents and discusses the implementation of society-based chemistry education, suitable teaching methods and student evaluation in practice. As one example, the article investigates teaching about life cycle of a product.